A Meta-Analytic Study of Social Presence in Higher Education Online Environments - Mykota, David (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance)

(untitled) (AU Press, 2025)
This study reports a systematic review and meta-analyses of the construct social presence in online higher education settings. The research objectives are to: 1) determine the overall impact of scale-based measures of social presence on student learning outcomes, and 2) determine the overall impact of scale-based measures of social presence on student satisfaction outcomes. A thorough examination of the research literature from 1995 to 2022 was conducted, employing a three-stage screening process to identify 53 studies suitable for inclusion in the meta-analyses. Utilizing a random effects model for analysis, the study investigated the two outcome measures with subgroup analysis. The results affirm that social presence has a moderate effect on both student satisfaction and learning outcomes, with no evidence of publication bias identified. In conducting a subgroup analysis to help explain some of the heterogeneity, significant effects were found for mode of delivery and for the scale-based instrument used. The paper concludes by advocating for enhanced rigour in research design to facilitate empirically validated investigations into improving social presence in online learning environments.